A Study on Conjugal Conflicts in Shashi Deshpande’s A Matter of Time - James, Jelsa Maria; Priscilla, R Margarat Joy (International Journal of Psychosocial Rehabilitation, 2020)
The paper titled “A study on Conjugal Conflicts in Shashi Deshpande’s A Matter of Time” mainly focuses on the relationship between man and women. Every individual wants to be enjoyed and valued by others. Women need more love than men, whereas a man prefers being respected by others especially by women. The study focuses deep into the female psyche that concentrates on various angles based on the relationship between the conjugal couples. The study explores the relational struggles and the vicious circle in relationships. This conflict arises not only because of misunderstandings but also because of the difference between the desires of man and women.